2012
DOI: 10.1021/nl203848t
|View full text |Cite
|
Sign up to set email alerts
|

Stable p-Type Conduction from Sb-Decorated Head-to-Head Basal Plane Inversion Domain Boundaries in ZnO Nanowires

Abstract: We report that Sb-decorated head-to-head (H-H) basal plane inversion domain boundaries (b-IDBs) lead to stable p-type conduction in Sb-doped ZnO nanowires (NWs) due to Sb and O codoping. Aberration-corrected Z-contrast scanning transmission electron microscopy shows that all of the Sb in the NWs is incorporated into H-H b-IDBs just under the (0001) NW growth surfaces and the (0001) bottom facets of interior voids. Density functional theory calculations show that the extra basal plane of O per H-H b-IDB makes t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
53
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(59 citation statements)
references
References 61 publications
6
53
0
Order By: Relevance
“…It has been demonstrated that a high doping concentration of Cl usually comes with enhanced formation of native defects such as vacancies, which migrate to the surface of ZnO NWs and form surface defects and thus induce rough surfaces . Similar phenomenon has also been observed for ZnO NWs doped with various dopants such as Sb, and Cu . The PL measurement results are shown in Figure a, which compares the normalized PL spectra measured from Cl‐ZnO NWAs/GF and undoped ZnO NWAs/GF.…”
Section: Resultssupporting
confidence: 53%
“…It has been demonstrated that a high doping concentration of Cl usually comes with enhanced formation of native defects such as vacancies, which migrate to the surface of ZnO NWs and form surface defects and thus induce rough surfaces . Similar phenomenon has also been observed for ZnO NWs doped with various dopants such as Sb, and Cu . The PL measurement results are shown in Figure a, which compares the normalized PL spectra measured from Cl‐ZnO NWAs/GF and undoped ZnO NWAs/GF.…”
Section: Resultssupporting
confidence: 53%
“…Other sources of p-type behavior, such as acceptors localized at stacking faults and Zn 2 D 3 precipitates, have been proposed, but seem less promising for creating efficient p-type material. Very recent work 11,12 has shown stable p-type nanowires due to Sb-decorated head-to-head basal plane inversion domain boundaries. Overall, the origin of the reported p-type conductivity remains uncertain in most cases.…”
Section: Introductionmentioning
confidence: 99%
“…14 Yankovich et al reported that Sb-decorated head-to-head basal plane inversion domain boundaries formed in Sb-doped ZnO nanowires upon codoping with Sb and O, leading to stable p-type conductivity. 15 Further insight into the origin of p-type conductivity in Sb-doped ZnO is required.…”
mentioning
confidence: 99%